Informational Aspects of Telepathology in Routine Surgical Pathology - Peter Gombas (Analytical Cellular Pathology)
Application of computer and telecommunication technology calls serious challenges in routine diagnostic pathology. Complete data integration, fast access patients' data to usage of diagnosis thesaurus labeled with standardized codes and free text supplements, complex inquiry of the data contents, data exchange via teleconsultation and multilevel data protection are required functions of an integrated information system. Increasing requirement for teleconsultation transferring a large amount of multimedia data among different pathology information systems raises new questions in telepathology. Creation of complex telematic systems in pathology requires efficient methods of software engineering and implementation. Information technology of object‐oriented modeling, usage of client server architecture and relational database management systems enables more compatible systems in field of telepathology. The aim of this paper is to present a practical example how to unify text based database, image archive and teleconsultation in a frame of an integrated telematic system and to discuss the main conceptual questions of information technology of telepathology.